2022
DOI: 10.3390/toxins14070432
|View full text |Cite
|
Sign up to set email alerts
|

Toolbox for the Extraction and Quantification of Ochratoxin A and Ochratoxin Alpha Applicable for Different Pig and Poultry Matrices

Abstract: Ochratoxin A (OTA) is one of the major mycotoxins causing severe effects on the health of humans and animals. Ochratoxin alpha (OTα) is a metabolite of OTA, which is produced through microbial or enzymatic hydrolysis, and one of the preferred routes of OTA detoxification. The methods described here are applicable for the extraction and quantification of OTA and OTα in several pig and poultry matrices such as feed, feces/excreta, urine, plasma, dried blood spots, and tissue samples such as liver, kidney, muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…In the reviewed studies, free OTA was found in all biological fluids studied, being more prevalent than its metabolites, which supports the low level of OTA biotransformation reported by some authors [129]. Regarding its metabolites, OTα was detected in feces and urine [109,114], and only small amounts were detected for OTB, the hydroxylated form of OTA, or phase II metabolites. Therefore, the parent compound was proposed as an OTA biomarker of exposure in both excreta and plasma samples [100,109,130].…”
Section: Biomarkers Of Exposuresupporting
confidence: 72%
See 3 more Smart Citations
“…In the reviewed studies, free OTA was found in all biological fluids studied, being more prevalent than its metabolites, which supports the low level of OTA biotransformation reported by some authors [129]. Regarding its metabolites, OTα was detected in feces and urine [109,114], and only small amounts were detected for OTB, the hydroxylated form of OTA, or phase II metabolites. Therefore, the parent compound was proposed as an OTA biomarker of exposure in both excreta and plasma samples [100,109,130].…”
Section: Biomarkers Of Exposuresupporting
confidence: 72%
“…The most commonly used extraction, clean-up, and enrichment procedures were liquid-liquid extraction (LLE) using various organic solvents (64% of the articles reviewed). Ethyl acetate (EtOAc) [44,100,109,114,116,126], ACN [39,44,48,49,107,116,118,119], MeOH [111,113,125], and their mixtures, such as MeOH/ACN [111], MeOH/EtOAc [44] and ACN/H 2 O [111,115,121,124], were the most commonly used solvents for mycotoxin LLE. Acid solutions were also employed to alter protein binding, thereby enhancing extraction efficiency [44,49,109,111,113,115,116,121].…”
Section: Biomarkers Of Exposurementioning
confidence: 99%
See 2 more Smart Citations